A study on customer's perception of Croatia's banking industry - Valentina Piric; Maja Martinovic; Zoran Barac (UTMS Journal of Economics, 2018)
Customer's perception is becoming more crucial for the banks to maintain their market shares, profitability and customer's loyalty under highly competitive market conditions. This paper studies the dimensions of customer's perception of the overall banking industry in Croatia, focusing on perception as a potential source of competitive advantage under the recently created negative public opinion towards the local banking industry. The purpose of this study is to provide an insight and deeper understanding how the banks, by developing a high level of positive customer perception while using a total set of available corporate communication activities, proper CRM activities and providing strong service quality, as well as tailor-made products, can develop a positive customer's perception as a strong source of sustainable competitive advantage and influence on customer's end choice, loyalty, profitability and market share during a time of economic crisis. A study was carried out in Croatia on the basis of 320 respondents as customers who have used different types of banking services in different banks. The results obtained confirm the convenience of analysing the importance of customer's perception on total banking business in the country, showing that perception strongly influences customer loyalty, market share and profitability of the business.
Keywords: M37; 330; corporate communication; competitive advantage; loyalty; market share; profitability